2021
DOI: 10.1155/2021/7765623
|View full text |Cite
|
Sign up to set email alerts
|

Combination of GLP-1 Receptor Activation and Glucagon Blockage Promotes Pancreatic β-Cell Regeneration In Situ in Type 1 Diabetic Mice

Abstract: Pancreatic β-cell neogenesis in vivo holds great promise for cell replacement therapy in diabetic patients, and discovering the relevant clinical therapeutic strategies would push it forward to clinical application. Liraglutide, a widely used antidiabetic glucagon-like peptide-1 (GLP-1) analog, has displayed diverse β-cell-protective effects in type 2 diabetic animals. Glucagon receptor (GCGR) monoclonal antibody (mAb), a preclinical agent that blocks glucagon pathway, can promote recovery of functional β-cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…However, the effect of GLP-1R on β-cell regeneration has not yet been investigated. Our recent report showed that the combination of GCGR mAb and liraglutide (a GLP-1R agonist) could not further increase β-cell area compared with GCGR mAb alone ( 48 ), suggesting that GCGR mAb itself already activated pancreatic GLP-1R sufficiently. By using the GLP-1R antagonist Ex9 and global and pancreatic Glp1r -knockout mice, our studies demonstrated that GLP-1R signaling contributed to GCGR antagonism–induced β-cell regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of GLP-1R on β-cell regeneration has not yet been investigated. Our recent report showed that the combination of GCGR mAb and liraglutide (a GLP-1R agonist) could not further increase β-cell area compared with GCGR mAb alone ( 48 ), suggesting that GCGR mAb itself already activated pancreatic GLP-1R sufficiently. By using the GLP-1R antagonist Ex9 and global and pancreatic Glp1r -knockout mice, our studies demonstrated that GLP-1R signaling contributed to GCGR antagonism–induced β-cell regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…REMD 2.59 is another human GCGR mAb that differs from volagidemab by one amino acid and has shown reduced gluconeogenesis and blood glucose, improved insulin action and glucose tolerance, enhanced lipid oxidation, protection against diabetic cardiomyopathy, and increased GLP-1 production and L-cell number in mouse models of type 2 diabetes [55][56][57]. REMD 2.59 has also been reported to decrease blood glucose, increase plasma glucagon, somatostatin, and insulin, increase α-cell mass and δ-cell number, which could potentially transdifferentiate into β-cells, and induce β-cell regeneration in normoglycemic and type 1 and 2 diabetic mouse models [58][59][60][61][62][63]. Additionally, this GCGR mAb has been tested for benefits in mouse models of myocardial infarction [64,65].…”
Section: Volagidemabmentioning
confidence: 99%
“…Moreover, we also show that dapagliflozin, an SGLT2 inhibitor, promotes α‐to‐β cell conversion in type 2 diabetic mice, although this conversion only accounts for a small fraction of the regenerated β cells. 12 Enhancement of GLP‐1 signaling by several approaches, including transfection of recombinant adenovirus expressing GLP‐1, GLP‐1 receptor agonists or dipeptidyl peptidase 4 (DPP‐4) inhibitors (which prevent degradation of GLP‐1 by DPP‐4), can induce α‐to‐β cell conversion in type 1 and type 2 diabetic rodents, 13 , 27 , 28 and increase β cell‐like gene expression in a subcluster of human α cells. 13 Either glucagon receptor blockage or dapagliflozin can upregulate GLP‐1 levels in the circulation and islets, which is suggestive of the importance of GLP‐1 in mediating α‐to‐β cell conversion.…”
Section: Transdifferentiation Of Pancreatic α Cellsmentioning
confidence: 99%